INFORMATION AND COMMUNICATION TECHNOLOGIES SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM EFEKTIF ERA TEKNOLOGI INFORMASI - Ismail Darimi (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2017)
Adapting to the technological era, learning activities are required to reduce the use of lecture methods and can be enriched in the use of instructional media, the role of learning media becomes increasingly important. ICT is a program, for tools, manipulation and convey information. The learning process of PAI can further facilitate the search for information, manipulation, management and transfer of science or transfer of information, so that the integration of ICT in the learning process becomes an important role in developing students' thinking ability, developing skills in the field of ICT to smooth the learning process, ICT especially in PAI lessons, and transforming schools into creative and dynamic learning institutions so that students are motivated, always curious in PAI learning. Broadly speaking media can be classified into graphics, audio, silent projections, games and simulations. Effective learning requires good planning of one of the media that will be used in the learning process. ICT is a very effective medium in learning PAI in the era of technology